Kemungkinan Money Laundering Dalam Pemilihan Kepala Daerah - arief amrullah (Jurnal Hukum IUS QUIA IUSTUM, 2005)
One of the prominent activities oforganized crime is to obtain profit that is obtained from Ulicit trafficking indnjgs, convption (foiinstance), orother proceds thatderived or obtained, directly or inderectly, through the commission ofan offence are entered into global financial system, so as if they become the proceed of the crime obtained from legal bussiness.Therefore, the effort to fight against money laundering is a dynamic process, and the organized criminals always seek thenewmethod toembody their illegal aim. One of them hands over their financial contribution to local government head election (Pilkada). The practice of money laundering in the Pilkada election very possibly occurs, because of the conditions which gives opportunity to organized crimes group to laundry their money inPilkada.